Strategi Pemerintah Desa dalam Pengembangan Wisata Danau Rana Kulan, Desa Rana Kulan, Kecamatan Elar, Manggarai Timur - Lusia Talia Ayu Naji (Public Service and Governance Journal, 2025)
This study aims to examine the village government's strategy in developing the tourism potential of Lake Rana Kulan, located in Rana Kulan Village, Elar Sub-district, East Manggarai Regency. The research uses a descriptive method with a qualitative approach. Data collection techniques include interviews, observation, and documentation, using both primary and secondary data sources. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The study adopts the tourism development components theory by Gunn (2002), which includes attraction, service/facilities, promotion, transportation, and information. The results show that the village government is working to develop tourism attractions such as the lake's natural beauty, fishing and swimming activities, as well as cultural attractions like festivals. In terms of facilities, gazebos, toilets, parking areas, a stage, and trash bins are available, although food stalls and accommodations remain limited. Basic infrastructure such as solar power (PLTS) and internet networks are in place, but clean water supply remains a challenge. Promotion is conducted through social media and cultural festivals, with plans to develop a village website. Road access to the location is still damaged but under repair, supported by local motorcycle taxi services. In terms of information, there are directional signs and digital access via Google Maps and the Jadesta website. Overall, the strategies implemented indicate the village government's commitment to tourism development, although infrastructure and facility limitations remain obstacles.